A novel mechanism of resistance to α-difluoromethylornithine induced by cycloheximide. Growth with abnormally low levels of putrescine and spermidine - Medrano, E.E. (1986)
Treatment of the chemically transformed fibroblasts BP-A31 and other cell lines with low concentrations of cycloheximide (CHM) for 72 h followed by the removal of the protein synthesis inhibitor leads to the proliferation of α-difluoromethylornithine (DFMO)-resistant phenotypes. These drug-resistant cells contain almost no ornithine decarboxylase (ODC) activity and concomitantly very low levels of putrescine and spermidine. Southern blot analysis and measurements of ODC activity and intracellular polyamine levels showed that the described mechanism of inducing resistance to DFMO triggered by CHM does not involve ODC gene amplification, altered transport of the drug or reduced affinity of the enzyme for DFMO. © 1986.